Notice of (1) Certain Bronze Implements from Dumfriesshire; and (2) a Symbol Stone from East Lomond Hill, Fife, recently presented to the National Museum - Corrie, John M (Proceedings of the Society of Antiquaries of Scotland, 1926)
A hoard from Greyfriars Church comprised four axes and two spearheads. Only three axes survive although there are plaster casts of all the objects in the National Museum. An axe from Dunscore and an axe and spearhead from Springfield Hill are also reported. A small slab discovered in East Lomond depicts a bull in a pecked design.